Human Health Risk Assessment and Exposure Evaluation by Monte-Carlo Simulation Method for Aflatoxin M1 in Widely Consumed Infant Dried Powder Milk in Iran - Behnaz Naghshbandi; Mohammad Ali Omrani; Abolfazl Jafari-sales; Abduladheem Turki Jalil; Navid Naghsh (Journal of Food Protection, 2023)
Monitoring aflatoxin M1 (AFM1) in dairy products and milk-based foods is very important. The main purpose of this research was to investigate and determine the amount and human health risk assessment of aflatoxin M1 (AFM1) in the most famous and widely used brands of infant dried powder milk (IDPM) consumed in Iran. For this study, 45 imported IDPM (IM-IDPM) samples and 45 domestically produced IDPM (DO-IDPM) samples (a total of 90 samples) were selected randomly. All samples were analyzed for AFM1 using a competitive enzyme-linked immunosorbent assay (ELISA) technique. The mean level and the percentage of positive samples for AFM1 in DO-IDPM were 9.2 ± 5.4 ng/kg and 73.3%, and for IM-IDPM, they were 5.1 ± 3.8 ng/kg and 33.3%, respectively. The average level of AFM1 in all samples was lower than the EU and Iranian national standards (25 ng/kg). AFM1 intake through IDPM consumption by Iranian infants less than one-year-old was lower than the allowable level, but the hazard quotient for infants less than 6 months was higher than the allowable level. Although the concentration of AFM1 in IDPM consumed in Iran is not hazardous, since Iranian infants may be exposed to AFM1 through other sources, including baby food, breast milk, raw and pasteurized milk, continuous monitoring of IDMP quality in Iranian markets should be taken.